TEMPORIZATION MATERIALS IN ORTHODONTICS: A DETAILED ANALYSIS OF SHEAR BOND STRENGTH - Al-Ghamdi, Abdulaziz Faisal Khalid; Al-Fayyad, Saud Ibrahim Nasser (International Research Journal Diagnostics, 2024)
In the contemporary digital age, there is a noticeable surge in the number of adults seeking orthodontic treatment to enhance their esthetics and address oral rehabilitation needs. Adult patients frequently present with complex dental issues, including missing teeth, multiple restorations, and artificial prostheses. Typically, the final restoration for such patients is postponed until the completion of orthodontic treatment. This situation necessitates orthodontists to bond brackets to provisional crowns and restorations throughout the entire orthodontic treatment duration. However, it has been observed that bonding brackets to provisional crowns poses unique challenges compared to bonding them to natural teeth. The purpose of this study is to explore the complexities and solutions related to this aspect of orthodontic treatment. Several studies have highlighted the increased difficulty of bonding brackets to provisional crowns compared to natural teeth. This challenge underscores the importance of using provisional crown materials with superior physical and mechanical properties. These materials must withstand occlusal and orthodontic forces while offering improved handling, enhanced esthetics, and biocompatibility with orodental tissues. Addressing these requirements is essential to ensure the success of orthodontic treatment in adult patients with complex dental conditions.